Saberes em movimento: aprendendo e ensinando a história da África no ensino médio - Valadares, Elka Regina Rodrigues (Universidade Federal do Tocantins, 2020)
The present research, developed within the scope of the Professional Master's Program ProfHistória, belongs to the line of research historical knowledge in the school space, has as its central theme to know the knowledge of the students about the History of Africa. From the present representations in the students' imagination, methodological strategies based on action research were developed to identify the knowledge. The research was developed in Colinas do Tocantins with students from the second grade of high school and used theoretical contributions from various fields. The participants researched, produced pedagogical material with the purpose of constructing and deconstructing knowledge about the history of Africa, relating them. The results show that the knowledge built by students in different spaces does not detract from the visions of different groups; according to recent research, but linked to a positive perspective of decolonization of knowledge, in the direction of producing a multicultural antiracist education, it is possible to design a new scenario in the formation of identities. In addition to the methodology applied to the students, the trajectory of struggles of social movements, especially the Black Movements, was investigated by the inclusion of African and Afro-Brazilian and indigenous culture and history in school curricula. This became a compulsory curricular component with Law 10.639 / 03, which was amended in 2008 by Law 11.645. The Law and its related legislation are part of a set of public policies adopted in Brazil since the 1990s, in compliance with the demands of the Social Movements to promote an antiracist and pluricultural education, ensuring that groups traditionally excluded from school spaces have their history and culture. The results can contribute to a reflection about the teaching of this subject as well as to the continued formation of teachers